2008
DOI: 10.1080/10635150802044011
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Phylogenetics of a Rapid Radiation in the Genus Thomomys (Rodentia: Geomyidae)

Abstract: Species complexes undergoing rapid radiation present a challenge in molecular systematics because of the possibility that ancestral polymorphism is retained in component gene trees. Coalescent theory has demonstrated that gene trees often fail to match lineage trees when taxon divergence times are less than the ancestral effective population sizes. Suggestions to increase the number of loci and the number of individuals per taxon have been proposed; however, phylogenetic methods to adequately analyze these dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 74 publications
6
95
1
Order By: Relevance
“…Concatenation methods infer phylogenies from multilocus sequences that are combined to form a single supermatrix (1), based on the assumption that all genes have the same or similar phylogenies (1,2). However, empirical studies have shown widespread presence of gene tree heterogeneity within mammals and other clades (3,4). When a high level of gene tree heterogeneity occurs in multilocus sequence data, theory and simulations have predicted that concatenation methods can yield misleading results (5,6).…”
mentioning
confidence: 99%
“…Concatenation methods infer phylogenies from multilocus sequences that are combined to form a single supermatrix (1), based on the assumption that all genes have the same or similar phylogenies (1,2). However, empirical studies have shown widespread presence of gene tree heterogeneity within mammals and other clades (3,4). When a high level of gene tree heterogeneity occurs in multilocus sequence data, theory and simulations have predicted that concatenation methods can yield misleading results (5,6).…”
mentioning
confidence: 99%
“…Like the deep coalescence approach, the Bayesian method does not rely on concatenated datasets but instead estimates gene tree distributions in a model in which gene trees are partially correlated due to their common species tree history . This method is implemented in the program Bayesian estimation of Species Trees (BEST) and has been shown to perform well in simulations (Edwards et al 2007) and can now handle multiple alleles per species (Belfiore et al 2008;Liu et al 2008).…”
Section: Statistical Phylogenetics: Estimating Species Treesmentioning
confidence: 99%
“…While the addition of > 300 species each of rodents and bats is unsurprising given their existing diversity, these clades may reasonably contain disproportionally high levels of cryptic diversity (e.g., Ruedi and Mayer 2001;Belfiore et al 2008), and thus the application of genetic sequence data may continue to yield greater insights. Within Eulipotyphla (most particularly in shrews), we expect that the discovery of new species will continue given their rate of recent discoveries and frequency of morphological crypsis (Esselstyn et al 2013).…”
Section: Discussionmentioning
confidence: 99%